Faster-Than-Nyquist 400 G Implementation Using 126-GBaud QPSK-OFDM With 88-GSa/s Undersampling - Liu, Peng; Chen, Hongxian; Ni, Weihao; Li, Fan (Frontiers in Physics, 2021)
In this paper, generation of 114 Gbaud and 126 Gbaud faster-than-Nyquist (FTN) Discrete Fourier Transform-spread (DFT-spread) quadrature phase shift keying orthogonal frequency division multiplexing (QPSK-OFDM) with 88-Gsa/s sampling rate digital-to-analogs (DACs) is experimentally demonstrated. It is the first time to realize 400G FTN DFT-spread QPSK-OFDM signal per optical carrier for metro and regional applications. In the FTN OFDM transmission system, frequency shaping is realized by a delay-and-add filter (DAF) at the transmitter to ensure the energy of signal is concentrated at low frequencies, which will make the OFDM much more robust to strong filtering effect to some extent. After pre-equalization, the bit error rate (BER) performance of 114 GBaud and 126 GBaud FTN DFT-spread QPSK-OFDM has been significantly improved, and Maximum likelihood sequence estimation (MLSE) has a better effect than binary decoding against the inter symbol interference (ISI) introduced by spectrum compression. The pay-load bit rate of dual polarization 126 Gbaud FTN DFT-spread QPSK-OFDM generated with 88 GSa/s sampling rate is 410.08 Gb/s, excluding all overhead including TSs, cyclic prefix (CP) and 20% forward error correction (FEC) coding. We successfully transmit 8×400 Gbit/s FTN DFT-spread QPSK-OFDM signal generated from 88 Gsa/s sampling rate DAC over 420 km single mode fiber (SMF) with the BER under 2.4×10-2.